Take filtering capability's soilless planting system - LIANG JIANFENG (2017)
The utility model particularly relates to a take filtering capability's soilless planting system, including support body, stock solution dish and a planting plate, a stock solution dish and a planting plate place respectively on the support body, wherein are equipped with the filter screen in the planting plate, and the both sides of filter screen are placed in on a planting plate's the lateral wall. The beneficial effects of the utility model are that: utilize the planting zone of filter screen in to a planting plate to filter, the debris of avoiding planting the in -process stop up the delivery port, in addition, be equipped with the recess in the planting plate, play the convenience and fix the filter screen in a planting plate. 本实用新型具体涉及种带过滤功能的无土种植系统，包括架体、储液盘和第定植盘，储液盘和第定植盘分别放置于架体上，其中第定植盘内设有过滤网，过滤网的两侧置于第定植盘的侧壁上。本实用新型的有益效果是：利用过滤网对第定植盘内的种植区域进行过滤，避免种植过程中的杂物堵塞出水口；另外，第定植盘内设有凹槽，起到方便将过滤网固定在第定植盘内。